Progressive Improvement of T-Scores in Men with Osteoporosis and Subnormal Serum Testosterone Levels upon Treatment with Testosterone over Six Years. (13th February 2014) - Haider, Ahmad; Meergans, Ulrich; Traish, Abdulmaged; Saad, Farid; Doros, Gheorghe; Lips, Paul; Gooren, Louis
Abstract : Testosterone deficiency leads to bone loss and testosterone treatment has a beneficial effect. This study investigated the effects of normalizing serum testosterone on bone mineral density in 45 men with osteoporosis, diagnosed with testosterone deficiency (serum testosterone levels < 12.1  nmol/L, T -scores: (mean ± SD) −3.12 ± 0.45, minimum: −4.10, and maximum: −2.60). In a cumulative, prospective, registry study of hypogonadal men (mean age: 53 ± 7 years) they received parenteral testosterone undecanoate of 1000 mg/12 weeks for up to six years. After one year 44 men were included in the registry, after two years 36 men, after three years 32 men, after four years 25 men, after five years 10 men and after six years 4 men. The declining numbers do not reflect drop-out rates but are a result of the registry design. Over the 6 year period there was a significant and progressive improvement of the T -scores in these men. Normalizing of serum testosterone leads to an improvement of bone mineral density and this improvement was progressive with the time period of testosterone administration. In this study of 6-years many men with testosterone deficiency suffered from classical diagnoses (Klinefelter's syndrome and testicular pathology) hitherto undiagnosed.